2010
DOI: 10.1007/s00540-010-0976-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single-dose dexmedetomidine on emergence agitation and recovery profiles after sevoflurane anesthesia in pediatric ambulatory surgery

Abstract: Intravenous DEX at a dose of 0.3 μg kg⁻¹ after induction of anesthesia reduced sevoflurane-associated EA and postoperative pain in pediatric ambulatory surgery, with no increase in the incidence of adverse events and with no change in parents' satisfaction level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(100 citation statements)
references
References 24 publications
7
90
2
1
Order By: Relevance
“…In our study, the incidence and severity of agitation score were significantly lower in group D compared to group L. Previous studies [11][12][13] showed that dexmedetomidine reduces the incidence of EA after sevoflurane anesthesia in children because of their sedative and analgesic effects. In another study, done by El-Hennawy et al [14]; dexmedetomidine and clonidine were administrated in a dose of 2 lg/kg as adjuvant with 0.25% bupivacaine caudally.…”
Section: Discussioncontrasting
confidence: 43%
“…In our study, the incidence and severity of agitation score were significantly lower in group D compared to group L. Previous studies [11][12][13] showed that dexmedetomidine reduces the incidence of EA after sevoflurane anesthesia in children because of their sedative and analgesic effects. In another study, done by El-Hennawy et al [14]; dexmedetomidine and clonidine were administrated in a dose of 2 lg/kg as adjuvant with 0.25% bupivacaine caudally.…”
Section: Discussioncontrasting
confidence: 43%
“…Details of the selection process are summarized in Figure 1. Dexmedetomidine was administered by single dose in 9 trials [9][11], [16][21], continuous infusion in 3 trials [22][24]. The placebo included saline in 11 trials [9][11], [16][22], [24] and lactated Ringer's solution in 1 trial [23].…”
Section: Resultsmentioning
confidence: 99%
“…25) Intravenous DEX significantly decreases the sevoflurane requirement 5,26) for anesthesia and EA during recovery. 5,27) Caudally administered DEX was also associated with a decreased sevoflurane requirement and increased the duration of postoperative sedation in children. 12,28) The sedative and analgesic properties of The proportion of the patients who did not request oral acetaminophen was significantly higher in the DEX than in Control group (p=0.029).…”
Section: Discussionmentioning
confidence: 99%